THE COMBINATION OF ORGANIC AND AFFECTIVE SYMPTOMS OF ELDERLY PATIENTS WITH DEPRESSION - Shadmanova L.Sh. (Web of Journals Publishing, 2025)
The psychopathological structure of affective disorders in elderly patients with organic brain diseases was represented by polymorphic symptoms, including symptoms of depressive and psychoorganic syndromes. The frequency of depressive disorders can vary depending on the severity of dementia.
Keywords: elderly patients, dementia, organic brain diseases, depressive disorders